Math Anxiety in Second and Third Graders and Its Relation to Mathematics Achievement - Wu, Sarah; Amin, Hitha; Barth, Maria; Malcarne, Vanessa; Menon, Vinod (Frontiers in Psychology, 2012)
Although the detrimental effects of math anxiety in adults are well understood, few studies have examined how it affects younger children who are beginning to learn math in a formal academic setting. Here, we examine the relationship between math anxiety and math achievement in 2nd and 3rd graders. In response to the need for a grade-appropriate measure of assessing math anxiety in this group we first describe the development of Scale for Early Mathematics Anxiety (SEMA), a new measure for assessing math anxiety in 2nd and 3rd graders that is based on the Math Anxiety Rating Scale. We demonstrate the construct validity and reliability of the SEMA and use it to characterize the effect of math anxiety on standardized measures of math abilities, as assessed using the Wechsler Individual Achievement Test (WIAT-II). Math achievement, as measured by the WIAT-II Math Composite score, was significantly and negatively correlated with SEMA but not with trait anxiety scores. Additional analyses showed that SEMA scores were significantly correlated with scores on the Math Reasoning subtest, which involves more complex verbal problem solving, but not with the Numerical Operations subtest which assesses basic computation skills. Our results suggest that math anxiety has a pronounced effect on more demanding calculations. Our results further suggest that math anxiety has an equally detrimental impact on math achievement regardless of whether children have an anxiety related to numbers or to the situational and social experience of doing math. Critically, these effects were unrelated to trait anxiety, providing the first evidence that the specific effects of math anxiety can be detected in the earliest stages of formal math learning in school. Our findings provide new insights into the developmental origins of math anxiety, and further underscore the need to remediate math anxiety and its deleterious effects on math achievement in young children.